RESILIENSI MAHASISWA KAMPUS V PAREPARE UNM (STUDI DESKRIPTIF PADA MAHASISWA PGSD KAMPUS V PAREPARE UNM) - musfirah musfirah (Universitas Negeri Makassar, 2020)
The purpose of this study was to determine the level of resilience of students at PGSD Campus V Parepare UNM. The research approach used in this study is a quantitative approach. The type of research used is quantitative descriptive. The level of resilience is seen from the seven indicators of ability according to Reivich and Shatte (2002), namely emotional regulation, impulse control, optimism, causal analysis, empathy, self efficacy, reaching out. Based on the results of the statistical descriptive statistical test, it was concluded that the level of resilience of the VSD Parepare UNM campus students on optimism indicators was in the very high category. On the indicators of emotion regulation, impulse control, and self efficacy are in the high category. In the causal analysis and empathy indicators are less high indicators and reaching out indicators are in the low category. although the level is different for each indicator, in general the resilience of students in the PGare V Campus Parepare is in the high category.